Вплив матеріалу катоду на суміщені катодні процеси у водних розчинах заліза (ІІ) сульфату - Кравченко, Кристина Миколаївна; Тульський, Геннадій Георгійович (Національний технічний університет "Харківський політехнічний інститут", 2022)
Розглянуто вплив матеріалу катоду на суміщенні катодні процеси у водних розчинах сульфатної кислоти. Підтверджено, що розроблена методика електрохімічної регенерації відпрацьованих розчинів сульфатно-кислотної обробки сталевих виробів вирішує проблему із утилізацією таких відпрацьованих сульфатних розчинів із включенням сульфатів заліза. Акцентовано увагу, що існуючі методи не є ефективними, зокрема, відпрацьовані сульфатні розчини нейтралізують лугом або відходами других виробництв, що містять тверді карбонати та гідроксиди. При цьому утворюються сульфатні відходи, що потребують захоронення на спеціальних полігонах. Під час проведення дослідів підтверджено, що застосування електрохімічної регенерації дає змогу катодно осадити залізо у вигляді фольги або металевого порошку, а через перебіг анодного процесу – перевести сульфати у сульфатну кислоту. Було встановлено кінетична закономірність суміщених катодних процесів у модельних розчинах заліза (ІІ) сульфату з сульфатною кислотою. У якості матеріалу катоду використовували платину та мідь. Вибір матеріалу катоду ґрунтувався на різних електрохімічних властивостях цих обраних металів по відношенню до водневої реакції. За результатами проведених вольтамперних досліджень було обґрунтовано катодну густину струму у діапазоні 0,02...0,04 А∙см⁻² для регенерації модельного водного розчину (моль∙дм⁻³ ): 0,5 заліза (ІІ) сульфату та 0,5 сульфатної кислоти для діапазону температур 290…293 К. Балансове дослідження з регенерації модельного розчину (моль∙дм⁻³ ): 0,5 заліза (ІІ) сульфату та 0,5 сульфатної кислоти проведено у трикамерному електролізері. Вихідний досліджуваний розчин подавався у середню камеру. Катодна густина струму складала 0,025 і 0,035 А∙см⁻² , робоча площа анода і катода – 85 см² . На катоді з 08Х12Н10Т одержали компактний осад заліза, який відшарувався. Аналіз катодного осаду показав наявність в залізі 0,065 % водню. Вихід за струмом заліза склав 92 %. Закінчення тафелевської ділянки перебігу катодного відновлення заліза з електрохімічним контролем відбувався через концентраційні обмеження по Fe²⁺ та омічний опір адсорбованого водню на межі гетерогенних фаз. Запропоновано усунути ці обмеження за рахунок перемішування електроліту.

Sulfuric acid is present in many enterprises for metal processing and manufacturing of metal parts. Existing methods of regeneration of spent solutions are not effective, in particular, spent sulfate solutions are neutralized with lye or waste from other industries containing solid carbonates and hydroxides. At the same time, sulfate waste is formed, which requires disposal at special landfills. Electrochemical regeneration of spent solutions of sulfate-acid treatment of steel solves the problem of disposal of such spent sulfate solutions with the inclusion of iron sulfates. The kinetics of combined cathodic processes in aqueous solutions of iron (II) sulfate at a concentration of 0.5 mol.∙dm⁻³ of iron (II) sulfate, depending on the cathode material was studied. The research methodology was as follows: model aqueous solutions with a composition (mol∙dm⁻³ ): 0.5 iron (II) sulfate with the addition of 0.5 sulfuric acid and a control solution – 1.0 sulfuric acid were prepared from chemicals of high stage of purification by dissolution in distilled water. The study of the kinetics of combined cathodic processes in model aqueous solutions was carried out by the method of linear voltammetry using the MTech PGP-500 S potentiostat. The auxiliary electrode is platinum. The reference electrode is mercury sulfate. Determination of iron (II) ions in the solution was carried out by the permanganatometric method. Based on the analysis of the obtained current-voltage curves, the effectiveness of the application of electrochemical regeneration of model solutions of iron (II) sulfate with sulfuric acid was established, which makes it possible to cathodically deposit iron in the form of foil or metal powder, and through the course of the anodic process - convert sulfates into sulfuric acid. During this process, oxidation of Fe²⁺ to Fe³⁺ takes place at the slightly soluble anode. Therefore, it is proposed to use polymer porous diaphragms to prevent Fe²⁺ from entering the anode space. Platinum and copper were used as cathode material. The choice of cathode material was based on different electrochemical properties of these metals in relation to the hydrogen reaction. The balance research on the regeneration of the model solution was carried out in a three-chamber electrolyzer. The initial test solution was fed into the middle chamber. The cathodic current density was 0.025 and 0.035 A∙cm⁻² , the working area of the anode and cathode was 85 cm². A compact iron deposit was obtained on the cathode with 08X12N10T, which peeled off. The analysis of the cathode deposit showed the presence of 0.065% hydrogen in iron. Output according to the current of iron was 92%. The end of the Tafel section of the course of cathodic reduction of iron with electrochemical control occurs due to Fe²⁺ concentration limitations and the ohmic resistance of adsorbed hydrogen at the boundary of heterogeneous phases. It is proposed to eliminate these limitations due to electrolyte mixing.
Influence of cathode material on combined cathode processes in aqueous solutions of iron (II) sulphate
Keywords: сульфатна кислота; кінетика; платина; мідь; металевий порошок; залізо; sulfate acid; platinum; kinetics; copper; metal powder; iron